1278 Work ability in breast cancer women survivors: a questionnaire-based study. (24th April 2018) - Bonfiglioli, R; Musti, MA; Collina, N; Stivanello, E; Giansante, C; De Lisio, S; Giordani, S; Morelli, C; Pandolfi, P
Abstract : Introduction: Breast cancer is the most common cancer in women worldwide. Early breast cancer diagnosis and improvement of therapeutic procedures have reduced the impact of treatment on function and increased the proportion of possibly employed survivors. The growth in female labour participation and the extension of working life have increased the number of women with breast cancer that work or have to face the issue of returning to work. The aim of the study was to identify predictors of reduced work ability at return to work among women treated for breast cancer. Methods: A questionnaire was sent to all 18–65 years old women resident and treated for breast cancer in Bologna Local Health Authority area in the period 2010–2012 to collect data about personal characteristics, medical history, breast cancer treatment work history and return to work. A multivariate logistic regression analysis was performed to identify predictors of reduced work ability among workingwomen. Results: A total of 1578 women were invited to fill in the questionnaire. The response rate was 53, 3%. Data of 503 workingwomen returned to work at the time of the study were analysed. Reduced work ability at return to work was reported by 43.5% women compared to the pre-diagnosis period. Reduced work ability was significantly more common in non-cohabiting than in cohabiting/married women, in labourers than in Office clerks/sales assistants and managers and more frequent after mastectomy than after breast-conserving interventions. Adjustments of work activities, occupational physician visits, less support from employer and colleagues and discrimination were significantly more frequently reported by women with a reduced work ability. Conclusion: Perceived reduced work ability is common in women who return to work after the treatment for breast cancer. Occupational physicians and GPs should be aware of a wide asset of factors to facilitate a successful return to work.